Speed running is determined by strength and power in young football players - Kuczek, Piotr; Nowak, Beata (Health Promotion & Physical Activity, 2020)
Introduction: For years researchers and trainers have been looking for determinants of sports talent in the youngest and also in the relationship between individual motor features relevant in given sport disciplines. There is a fundamental consensus in the opinion that the strength and power of the lower limbs are correlated with the speed of running. However, this relationship also among the youngest is not so clear. The purpose of the work was to show the relationship between strength and power generated during vertical jump and achieved height jump and the speed of flat running in the youngest footballers. Material and methods: The research covered 75 children training football at the age of 6–14 years divided into two age groups. The subjects made a countermovement jump on a dynamometric platform measuring strength, power, speed of rebound and the height obtained, after which they performed a flying run over a distance of 20 m. Results: A strong, positive correlation was demonstrated between all dynamic and kinetic parameters of the jump and running speed. This correlation turned out to be clearly stronger in the older group of football players than in the younger group. Conclusions: The obtained results suggest that strength and power are good predictors, such an important feature in football as the player’s motion speed, already at the basic level of training.